2017
DOI: 10.1186/s40413-017-0177-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender aspects and influence of hormones on bronchial asthma – Secondary publication and update

Abstract: There is good evidence for gender-specific differences in asthma regarding all affected areas, from intra-to extracellular mediators to the whole organ structure und functioning of the lung. These result from complex, in parts synergistic, in other parts opposing, effects -especially of female sex hormones, and rather protective effects of male hormones against asthma, which include effects on the cellular immune system. Additionally, there are gender differences of sociocultural origin, regarding presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 60 publications
3
34
1
8
Order By: Relevance
“…6 This damage worsens with long-term exposure, causing remodelling, reduced lung function, and increased airway reactivity and sensitivity to future exposures, including allergens. 12 Although we corroborated that boys have more childhood allergy and asthma than girls, 29 in this study we found a trend to a stronger association between use of cleaning products and outcomes in girls than boys, although this sex difference was not statistically significant. A study involving adults and children with asthma found that males had higher eosinophil and immunoglobulin E levels than females, 30 raising interest in sex-dependent biologic al mechanisms for asthma development.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…6 This damage worsens with long-term exposure, causing remodelling, reduced lung function, and increased airway reactivity and sensitivity to future exposures, including allergens. 12 Although we corroborated that boys have more childhood allergy and asthma than girls, 29 in this study we found a trend to a stronger association between use of cleaning products and outcomes in girls than boys, although this sex difference was not statistically significant. A study involving adults and children with asthma found that males had higher eosinophil and immunoglobulin E levels than females, 30 raising interest in sex-dependent biologic al mechanisms for asthma development.…”
Section: Discussioncontrasting
confidence: 41%
“…A study involving adults and children with asthma found that males had higher eosinophil and immunoglobulin E levels than females, 30 raising interest in sex-dependent biologic al mechanisms for asthma development. Some researchers have postulated the role of hormones as a biological explanation for these differences, 29,31 but understanding nonhormonal biological differences can inform interventions. A 2005 study involving school children in Saskatchewan found the relation between home mould exposure and asthma to be more prominent in girls than in boys.…”
Section: Discussionmentioning
confidence: 99%
“…More prevalently and severely in pubescent males after puberty, there occurs a gender switch. In men aged 45 or more, increases in the risk of asthma severity and in the elderly differences related to gender diminish [48]. The MeDALL study showed an higher prevalence of asthma, rhinitis, and respiratory multimorbidity in boys before puberty and a sex balanced estimated prevalence after puberty [49].…”
Section: Asthma and Rhinitismentioning
confidence: 99%
“…This may explain the different OR values observed for men and women in this work because there appear to be gender-based differences in immune responses 33–35. These differences are not well understood but similar effects have been seen for asthma 36 37…”
Section: Discussionmentioning
confidence: 70%